2015
DOI: 10.1136/jclinpath-2015-203044
|View full text |Cite
|
Sign up to set email alerts
|

The use of whole-genome sequencing for molecular epidemiology and antimicrobial surveillance: identifying the role of IncX3 plasmids and the spread ofblaNDM-4-like genes in the Enterobacteriaceae

Abstract: This study highlights the potential role that IncX3 plasmids have played in the emergence and dissemination of blaNDM-4-like variants worldwide and emphasises the importance of resistance gene surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 19 publications
3
41
1
Order By: Relevance
“…bla was carried by an IS26-dsbC-trpF-ble MBL -bla NDM-7 -⌬ISAba125-IS5-⌬ISAba125 genetic element; this is the same structure as that of the bla NDM-4 -and bla NDM-5 -containing elements reported previously (34,35) and is similar to the bla NDM-7 plasmid described from Germany (27). The overall plasmid genome synteny in pKpN01-NDM7 is also identical to that of bla NDM-5 -harboring pNDM_MGR194 (from a ST11 K. pneumoniae isolate in India) (34) and bla NDM-4 -harboring pJEG027 (from a K. pneumoniae isolate in Australia) (35). Importantly, IS5 was inserted into ISAba125 located upstream of bla NDM , leading to the interruption of ISAba125 into two segments (1,018 bp and 73 bp) (Fig.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…bla was carried by an IS26-dsbC-trpF-ble MBL -bla NDM-7 -⌬ISAba125-IS5-⌬ISAba125 genetic element; this is the same structure as that of the bla NDM-4 -and bla NDM-5 -containing elements reported previously (34,35) and is similar to the bla NDM-7 plasmid described from Germany (27). The overall plasmid genome synteny in pKpN01-NDM7 is also identical to that of bla NDM-5 -harboring pNDM_MGR194 (from a ST11 K. pneumoniae isolate in India) (34) and bla NDM-4 -harboring pJEG027 (from a K. pneumoniae isolate in Australia) (35). Importantly, IS5 was inserted into ISAba125 located upstream of bla NDM , leading to the interruption of ISAba125 into two segments (1,018 bp and 73 bp) (Fig.…”
Section: Resultsmentioning
confidence: 61%
“…However, we were unable to establish such a link. pKpN01-NDM7 is an IncX3 plasmid; IncX3 plasmids are usually self-transferable and have been associated with the spread of several antimicrobial-resistant genes, including carbapenemase genes, such as bla NDM (33)(34)(35)(36)(37), bla KPC (38), and bla OXA-181 (39,40). A BLAST search against the GenBank sequence database revealed that pKpN01-NDM7 is highly similar to other bla NDMharboring IncX3 plasmids, including pNDM-HN380 (bla NDM-1 ) (36), p112298-NDM (bla NDM-1 ; GenBank accession number KP987216), pEc1929 (bla NDM-5 ; GenBank accession number KT824791), pNDM_MGR194 (bla NDM-5 ) (34), pJEG027 (bla NDM-4 ) (35), and pOM26-1 (bla NDM-7 ; GenBank accession number KP776609) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, NDM-producing Enterobacteriaceae have been reported in Australia (27,28). Limited studies have described the plasmid features and genetic contexts of NDM producers from Australia (29)(30)(31). Here, we analyze the bla NDM genetic contexts of 12 NDM-producing Enterobacteriaceae isolates from Australia between 2012 and 2014 to provide insights into their likely acquisition.…”
mentioning
confidence: 99%
“…In GenBank deposit AB898038 (19), an IS6 family transposase truncates the ISAba125 and an unknown transposase is present 2.367 kb downstream from the bla NDM-3 gene. In K. pneumoniae plasmid pJEG027 (20), an IS5 family transposase truncates the ISAba125 and IS26 is found 2.189 kb downstream from the bla NDM-4 gene. A similar genetic structure is present in GenBank deposits KP826705 (unpublished) and KP178355 (21), containing, respectively, the bla NDM-7 and bla NDM-5 genes.…”
mentioning
confidence: 99%